A New Frontier: Palestinian English Teachers’ Experiences and Needs for Social-Emotional Learning Integration in EFL Classrooms - Wafa Hiwari; Anwar Abdel Razeq; Luis Javier Pentón Herrera (Anglica. An International Journal of English Studies)
This qualitative case study explores the integration of social-emotional learning in Palestinian English as a foreign language classrooms. Ten Palestinian EFL teachers were interviewed, revealing a universal recognition of SEL’s importance but limited implementation due to challenges such as inadequate knowledge, curriculum demands, and lack of professional development. The study identifies a critical need for explicit SEL integration in curricula and teacher education. Findings highlight teachers’ eagerness to incorporate SEL, contingent on support and resources. We end by discussing the necessity for comprehensive SEL initiatives in Palestinian education, considering socio-political contexts and the pivotal role of teacher preparedness and resource availability.